2004
DOI: 10.1023/b:egah.0000039594.19432.80
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Heavy Metals in Surface Sediments of Taihu Lake, East China

Abstract: The BCR (European Communities Bureau of Reference) three-step sequential extraction procedure was applied to fractionate heavy metals in the sediment of Taihu Lake. For the determination of total metal concentration of the sediments, sample digestion was achieved by using HF/H 2 O 2 /HNO 3 (2/1/1) acid mixture in a microwave-irradiated closed vessel system. The concentrations of Cd, Ni, Cr, Zn, Cu and Pb in various extracts solutions were analyzed by Inductively Coupled Plasma Atomic Emission Spectrometry (ICP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 11 publications
2
42
0
3
Order By: Relevance
“…A special application was prepared, which enabled 52 Cr isotopes measurement in the DRC mode and 75 As, 55 Mn, 60 Ni, 65 Cu, 66 Zn, 114 Cd, 75 As, 208 Pb measurements in the standard mode. Methodology for the determination of metals/metaloids using ICP-MS spectrometer was presented in [24].…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…A special application was prepared, which enabled 52 Cr isotopes measurement in the DRC mode and 75 As, 55 Mn, 60 Ni, 65 Cu, 66 Zn, 114 Cd, 75 As, 208 Pb measurements in the standard mode. Methodology for the determination of metals/metaloids using ICP-MS spectrometer was presented in [24].…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…Sediments are a significant reservoir and source of metals in the aquatic environment and mediate transport and storage of hazardous metals (Guevara et al 2005;Moriilo et al 2004). The concentration of heavy metals and metalloid in sediments from polluted aquatic environments may be hundreds or even tens of thousands of times greater than sediments from non-polluted aquatic environments (Wang et al 2002). Consequently, understanding the spatial distribution of heavy metals in sediments can provide the evidence of the anthropogenic impacts and is critical for environmental management and decision-making.…”
Section: Introductionmentioning
confidence: 96%
“…However, the presence of pedogenic iron oxide phases may also influence the sorption capacity of this sample as this sample is characterized by the highest reducible iron content in this profile (see Table 1). Many studies have shown that the iron-oxide phases in soils may significantly contribute to the adsorption of these metals, especially for Pb and Zn [44,45].…”
Section: Discussionmentioning
confidence: 99%